2012
DOI: 10.1016/j.neulet.2012.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signals induced by FGF-2 in parasympathetic neurons: Role of second messenger pathways

Abstract: Basic Fibroblast growth Factor, or FGF-2, has been shown to promote neuronal survival and neurite outgrowth in dissociated neurons from the embryonic chick ciliary ganglion; in these effects the propose that this complex behaviour can be due to a perturbation in PIP 2 levels at the plasmamembrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…The increases in [Ca 2+ ] i showed a markedly different time course in the two compartments: at the soma the response was in most cases a smooth and gradual increase in [Ca 2+ ] i , followed by either a maintained or a slowly decaying plateau (Fig. 5B, left), in accordance with the responses observed at 24 h [13,61]. In some cases, the plateau was preceded by a transient phase, indicative of a possible contribution of release from intracellular stores, that has been previously [13] observed in a subpopulation of cells.…”
Section: Spatial Localization and Specificity Of Fgf-2 Induced Calciusupporting
confidence: 79%
See 1 more Smart Citation
“…The increases in [Ca 2+ ] i showed a markedly different time course in the two compartments: at the soma the response was in most cases a smooth and gradual increase in [Ca 2+ ] i , followed by either a maintained or a slowly decaying plateau (Fig. 5B, left), in accordance with the responses observed at 24 h [13,61]. In some cases, the plateau was preceded by a transient phase, indicative of a possible contribution of release from intracellular stores, that has been previously [13] observed in a subpopulation of cells.…”
Section: Spatial Localization and Specificity Of Fgf-2 Induced Calciusupporting
confidence: 79%
“…Therefore, it is likely that in the CG it acts as a paracrine/autocrine factor, rather than as a target-derived one. It must be recalled that, even if our data are obtained from mixed cultures, we have previously shown that the role of FGF-2 is cell autonomous [61].…”
Section: Discussionmentioning
confidence: 94%
“…**P < 0.01, ***P < 0.001 compared with 0 ng/mL rFGF2. reported in somatic cells (Munaron et al 1995, Zamburlin et al 2012, Liu & Schneider 2014. In our experimental conditions, sperm incubation with rFGF2 also resulted in an increase in acrosomal exocytosis.…”
Section: Discussionsupporting
confidence: 58%
“…Currently, there is insufficient information regarding decreased cell function and mortality in relation to intracellular calcium levels. Calcium is a secondary cellular messenger that is required for complex functions in diverse types of cells, including the regulation of gene expression, muscle contraction and molecular transport, as well as the amplification of the action of ligands on the cell surface (Zamburlin et al , ; Schwarz et al , ). The calcium ion is regulated through a number of highly complex mechanisms, including pumps, ion channels and intracellular reservoirs.…”
Section: Introductionmentioning
confidence: 99%